Tolerance to manganese by bacteria isolated in an area contaminated by mining tailings (Research, Society and Development, 2022)
The aim of this study was to isolate bacteria present in mining tailings and assess their tolerance to manganese metal. The isolation of microorganisms was carried out from the tailings collected in the municipality of Mariana, Minas Gerais, from the area contaminated by mining mud as a result of the Fundão dam failure. Four isolates were obtained, which were submitted to Gram stain and manganese tolerance tests. The experimental design used was completely randomized with six treatments and three replications, with each Petri dish constituting an experimental unit. The isolates BRM1 and BRM2 were the most tolerant to manganese, showing good prospects for application in areas contaminated by this metal.